Enhancing Grip Strength and Manual Dexterity in Unilateral Cerebral Palsy: A Randomized Trial of Mirror Visual Feedback vs. Modified Constraint-Induced Movement Therapy - Mohamed A. Abdel Ghafar; Osama R. Abdelraouf; Nouf H. Alkhamees; Mariam E. Mohamed; Eman M. Harraz; Mohamed K. Seyam; Zizi M. Ibrahim; Amani Alnamnakani; Amal A. Elborady; Rafik E. Radwan (Brain Sciences)
Background/Objectives: Manual dexterity and hand strength are common challenges in children with unilateral cerebral palsy (UCP), limiting the use of their affected upper limb and impacting daily activities. The efficacy of a long-duration Mirror Visual Feedback (MVF) program compared to Modified Constraint-Induced Movement Therapy (mCIMT) in addressing these issues remains unreported. This study was conducted to compare the efficacy of mCIMT and MVF in improving manual dexterity and hand strength in children with UCP. Methods: Fifty children with UCP (aged 5–9 years) were randomly assigned to either the MVF or mCIMT group. Children in both groups received their respective interventions for 30 min, five times per week, over 12 weeks. Additionally, all participants underwent traditional physical therapy for 12 weeks, three times per week, with each session lasting 45 to 60 min. Manual dexterity was assessed using the Box and Block Test (BBT), and maximum isometric hand strength was measured with a hydraulic handheld dynamometer. Evaluations were conducted before the intervention and 12 weeks later. Results: Repeated measures of MANOVA revealed significant enhancements in manual dexterity and hand strength in both groups after the intervention. However, the mCIMT group demonstrated significantly greater gains in BBT scores (p = 0.014) and maximum isometric hand strength (p = 0.017) compared to the MVF group, with effect sizes of 0.75 and 0.79, respectively. Conclusions: Incorporating either mCIMT or MVF into rehabilitation significantly enhances manual dexterity and hand strength in children with UCP, with mCIMT yielding superior outcomes.